Global uniqueness results for Hadamard fractional integral equations (Nonlinear Studies, 2023)
In this paper we investigate the existence and uniqueness of solutions of partial Integral Equations via Hadamard's fractional integral, by applying a nonlinear alternative of Leray-Schauder due to Frigon and Granas for contraction maps on Fréchet spaces.